PEMBARUAN HUKUM WARIS ISLAM DI INDONESIA - Muhibbuddin, Muhammad (Ahkam: Jurnal Hukum Islam, 2015)
This article discusses one of the agenda reforming Islamic law about inheritance for the descendant of different religion. According to the Decree of the Supreme Court Number: 368 K/AG/1995 on and number Nomor: 51 K/AG/1999 it is possible for non muslim descendants to receive inheritance through wajibah. Kata kunci: Pembaruan, Hukum Waris Islam